Stretchable microwave absorbing and electromagnetic interference shielding foam with hierarchical buckling induced by solvent swelling. (February 2020) - Huang, Kun; Chen, Mengmeng; He, Gang; Hu, Xiaoyu; He, Wenqian; Zhou, Xiang; Huang, Yi; Liu, Zunfeng
Abstract: Wearable devices and morphing aircrafts require stretchable microwave absorbing (MA) and electromagnetic interference (EMI) shielding materials, which could work as EMI shielding clothes and battleplane coatings. Although conductive foams could work well in both microwave absorption and EMI shielding, their performances under stretching have not been studied thus far, which is possibly due to the difficulty in maintaining the electrical conductance under stretching. Herein, a carbon nanotube/polyurethane (PU) foam with hierarchical buckling structure is prepared as a stretchable MA and EMI shielding material. The foam is fabricated by dip-coating PU foam in carbon nanotube/organic solvent solution. The PU foam swells in organic solvents and forms hierarchical buckling structures upon drying. After reinforcement with Ecoflex, the composite shows a suitable degree of stability in its resistance during stretching. Hierarchical buckling can maintain the conductance during stretching and enhance the attenuation of EM waves. A minimum microwave absorption reflection loss of −35.6 dB at a 10% strain level in 2–18 GHz and an average EMI shielding effectiveness of 20.2 dB at a 30% strain level in X-band are achieved. These results represent a new step towards the application of elastic and stretchable electronic materials for electromagnetic wave protection. Graphical abstract: Image 1